Safety & efficacy of manual vacuum aspiration compared to dilatation & curettage in the management of early pregnancy failure (Bangladesh Medical Journal Khulna, 2017)
Background: Early pregnancy failure is a major health problem across the globe. This is particularly important for the woman of Bangladesh.Objective: The aim of our study was to evaluate the safety and efficacy of manual vacuum aspiration (MVA) compared to dilatation and curettage (D&C) in the management of first trimester abortion.Methods: This was a prospective randomised study done in Obstetrics & Gynaecology department of Jessore medical college & Khulna medical college. Over a period of one year from January 2014 to December 2014, a total of four hundred women presented with spontaneous miscarriage with gestational age < 12 weeks patients with no sign of septic abortion and no history of pregancy with fibroid uterus were included in the study.Results: These patients underwent random selection either MVA group (n = 200) or D&C group (n=200). Cases were compared with respect to age, parity, gestational age, risk, blood loss, time taken & complications. The distribution of age, parity & gestational age was similar in both groups. The mean duration of procedure was significantly higher (P